Urinary Tract Infection and Medicinal Importance of Anacardium Occidentale (International Journal of Scientific Research in Science and Technology, 2026)
Urinary tract infections (UTIs) are common infectious diseases affecting the urinary system, with a higher incidence in women and children. They are mainly caused by pathogenic microorganisms such as Escherichia coli, Klebsiella spp., Proteus spp., and Staphylococcus spp. The growing problem of antimicrobial resistance has increased interest in medicinal plants as alternative or supportive therapies. Anacardium occidentale L. (cashew) is a traditionally important medicinal plant known for its wide range of therapeutic properties. Different parts of the plant, including leaves, bark, nuts, and shells, contain bioactive compounds such as anacardic acids, flavonoids, tannins, and phenolic compounds. These constituents possess antimicrobial, anti-inflammatory, antioxidant, and wound-healing activities. Scientific studies have reported that extracts of A. occidentale show inhibitory effects against several uropathogenic bacteria, indicating its potential usefulness in the management of urinary tract infections. This abstract emphasizes the causes and significance of UTIs and highlights the medicinal importance of Anacardium occidentale as a natural source for developing effective plant-based therapies.